Separation of Ketorolac enantiomers on polysaccharide‐based chiral stationary phases using a polar organic mobile phase. Issue 5 (May 2018) - He, Yunchao; Wu, Yaling; Cheng, Lingping; He, Shanshan; Wang, Qiuhua; Wang, Huiying; Ke, Yanxiong
Abstract: Ketorolac has been widely applied in clinical medicine for its antipyretic, analgesic and anti‐inflammatory pharmacological activity. Research showed that the analgesic effect of the S enantiomer is 230 times stronger than that of the R enantiomer. Getting the high‐purity S enantiomer of Ketorolac has profound significance but still remains a challenging topic. In this work, the separation of the R and S enantiomers of Ketorolac was investigated on polysaccharide‐based chiral stationary phases. Chiralcel AD‐H, OD‐H, OJ‐H and AS‐H columns were evaluated using polar organic and normal phase mode, respectively, in which the OJ‐H column showed the best performance with high selectivity and resolution for Ketorolac with α = 2.43 and R S = 9.04 by using methanol/formic acid (100:0.1, v/v) as the mobile phase. The influences of acid additive, composition of mobile phase and temperature were examined. The coating amount of cellulose tris‐ (4‐methylbenzoate) has significant influence on the sample loadability. The high loadability of chiral stationary phases coated with 40% of cellulose tris‐ (4‐methylbenzoate) allows preparative separation up to 16 mg on an analytical column of 250 × 4.6 mm id in a single run for Ketoroac using methanol/formic acid (100:0.1, v/v) as mobile phase, which shows a potential application in industrial preparation.